Strategic technology management practices in select auto component joint ventures in India: a case study using SAP-LAP methodology. (22nd August 2011) - Sahoo, Tapan; Banwet, Devinder Kumar; Momaya, K.
The automobile industry in India has gone through a lot of transformation since inception. With the liberalisation process starting in 1991, the industry has seen the entry of global auto majors in India. Due to changing customer preferences, environmental regulations, concern for safety and inclination towards entertainment, the role of technology in the auto industry has assumed great significance. In line with the global auto and auto component industry, the auto component companies in India has also gone in for technical alliances (TA), joint ventures (JV) with global auto component manufacturers, which seems to have impacted their technology management practices. This paper covers the longitudinal study of technology development at two joint venture auto component manufacturers. The methodology employed for this study is a combination of literature survey, expert opinion, comparative case analysis and SAP-LAP, a flexible systems methodology. The study finds that effective strategic technology management can contribute to faster technology absorption and overall business performance. The two cases provide valuable insights into the strategic technology management practices in joint venture organisations and exhibit the methodology adopted by the companies in their evolutions towards becoming the world-class integrated organisations.